2011
DOI: 10.1002/ijc.26076
|View full text |Cite
|
Sign up to set email alerts
|

An intact retinoblastoma protein‐binding site in Merkel cell polyomavirus large T antigen is required for promoting growth of Merkel cell carcinoma cells

Abstract: Merkel cell carcinoma (MCC) is a highly aggressive skin cancer that frequently harbours Merkel cell polyomavirus (MCV) DNA integrated in the genome of the tumor cells. In our study, we elaborate our recent finding that MCV-positive MCC cell lines require the expression of the viral T antigens (TA). Indeed, in a xeno-transplantation model, we prove that TA expression is essential also in an in vivo situation, as knock down of TA leads to tumor regression. Moreover, rescuing TA short hairpin RNA (shRNA)-treated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
254
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 193 publications
(274 citation statements)
references
References 37 publications
4
254
0
Order By: Relevance
“…MCPyV LT promotes oncogenesis partially through the highly conserved LXCXE motif, which binds to Rb [24]. Rb normally sequesters the transcription factor E2F, however, LT binding to Rb releases E2F resulting in increased expression of cyclin E and CDK2.…”
Section: Mcpyv Biologymentioning
confidence: 99%
“…MCPyV LT promotes oncogenesis partially through the highly conserved LXCXE motif, which binds to Rb [24]. Rb normally sequesters the transcription factor E2F, however, LT binding to Rb releases E2F resulting in increased expression of cyclin E and CDK2.…”
Section: Mcpyv Biologymentioning
confidence: 99%
“…13,14 Emerging data implicate maintenance and expression of the polyomavirus large T antigen in cell cycle dysregulation and the pathogenesis of viral transformation leading to Merkel cell carcinoma. 12,[15][16][17][18][19][20][21] Although the molecular role of Merkel cell polyomavirus is quickly evolving, the overall biology of Merkel cell carcinoma is poorly understood. Moreover, the presence of polyomavirus alone is not sufficient for carcinogenesis, namely in those Merkel cell carcinoma cases considered as polyomavirusnegative.…”
mentioning
confidence: 99%
“…To this end, we used an shRNA targeting both LTA and sTA because the only available LTA specific shRNA induces also considerable off target effects. 6 Moreover, TA shRNA induced growth inhibition can be rescued by ectopic expression of shRNA insensitive LTA (data not shown) indicating that in our TA shRNA system sTA knockdown does not affect cellular growth significantly. In accordance with previous published data, knockdown of TA in MCVþ MCC cells resulted in decreased LTA and survivin protein expression (Fig.…”
Section: Dear Editormentioning
confidence: 83%
“…This rescue, however, was abrogated when a point mutation in the LTA protein interfering with LTA binding to the retinoblastoma protein (RB) was introduced. 6 In a recent publication, Arora et al reported increased expression of survivin in MCVþ compared with MCV-MCC cases. 7 Survivin is an inhibitor of apoptosis protein family member that contributes to many human cancers by promoting cell survival and cell division.…”
Section: Dear Editormentioning
confidence: 97%